Enforcement Comparison Law To Marijuana Drug Abuse In Indonesia And Canada - Amonrat Ammartsena; Soviq Awabin; Piki Arjuna; Pasya Ayu Mashanda; Prasetio Agung Wibowo; Pina Endriyan Sinta (Universitas Malayati, 2025)
Enforcement law to abuse narcotics type marijuana show difference fundamental between Indonesia and Canada. In Indonesia, marijuana categorized as narcotics group I, with enforcement law of a nature repressive and focused on prevention as well as eradication use and distribution. Sanctions applied covers punishment harsh prison terms and high fines. In Canada, on the other hand, marijuana has legalized For use medical and recreational under cannabis act since 2018. Policy in Canada is more emphasize on regulation, reduction danger, and health society, with enforcement law directed at production and distribution illegal outside framework existing regulations. This study aims to analyze the comparative law enforcement against marijuana abuse in Indonesia and Canada. Using a qualitative descriptive method, this study presents the results related to the legal policies in force in both countries. In Indonesia, marijuana is classified as a class I narcotic based on Law No. 35 of 2009, with a strict legal approach without tolerance. Meanwhile, in Canada, marijuana is legalized through the 2018 Marijuana Act, with a policy that prioritizes legality and rehabilitation. Although the two countries have different approaches, both use positive law as the basis for imposing sanctions. Based on study This obtained conclusion namely Indonesia and Canada have different and similar views regarding law enforcement regarding the abuse of narcotics such as marijuana, apart from that it is different from Indonesia, Canada in enforcing the law on marijuana abuse actually issued the Cannabis Act as a form of legalization of marijuana narcotics, the Cannabis Legalization Act (The Cannabis Act). From this conclusion, the author can provide advice that Indonesia needs to continue to develop legal policies that not only emphasize severe punishment but also consider aspects of rehabilitation for drug abusers, in addition there is a program to adopt several approaches implemented in Canada, such as strengthening rehabilitation programs for marijuana abusers, can be an effective alternative in handling drug abuse cases. Kata Kunci : Law Enforcement, Drug Abuse, Marijuana